SAHR Tuesday Talks - The documents of the undocumented - ICA (ICA, 2025)
How legal processes generate records that transform individuals often labeled as “undocumented” into holders of official files, essential for defending their rights and preserving their personal histories.
Worldwide

SAHR Tuesday Talks - Managing UNHCR Records - ICA (ICA, 2025)
Managing UNHCR Records, Archives and Protecting Information on Refugees and Displaced Persons
Worldwide